2018
DOI: 10.1016/j.talanta.2018.03.101
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative fluorophore labeling of carbohydrates via reductive amination

Abstract: As analytical glycomics became to prominence, newer and more efficient sample preparation methods are being developed. Albeit, numerous reductive amination based carbohydrate labeling protocols have been reported in the literature, the preferred way to conduct the reaction is in closed vials. Here we report on a novel evaporative labeling protocol with the great advantage of continuously concentrating the reagents during the tagging reaction, therefore accommodating to reach the optimal reagent concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…The influence of concentration, temperature, time, [28] the nature of acid [29] and reducing agent [10d] were optimized for APTS . Further improvements such as evaporative reductive amination have been published recently [30] . We found that the new compounds PCN and PAZ are applicable for reductive amination of sugars under water‐free conditions (2‐picoline–borane complex and malonic acid) reported previously for PSN and PSU dyes [18] .…”
Section: Resultsmentioning
confidence: 59%
“…The influence of concentration, temperature, time, [28] the nature of acid [29] and reducing agent [10d] were optimized for APTS . Further improvements such as evaporative reductive amination have been published recently [30] . We found that the new compounds PCN and PAZ are applicable for reductive amination of sugars under water‐free conditions (2‐picoline–borane complex and malonic acid) reported previously for PSN and PSU dyes [18] .…”
Section: Resultsmentioning
confidence: 59%
“…In this study, the effect of processing conditions on the global N-glycosylation profile of human blood samples was investigated by CE-LIF with special attention on the fate of sialylated structures. Recently reported new sample preparation protocols were applied to accommodate the high complexity of the human blood N-glycome, including temperature adjusted denaturation and evaporative labeling protocol [24,25]. First, the global N-glycosylation profile of whole human blood was analyzed in as native form as rationally possible in order to establish a reference state for the consequent comparisons [26].…”
Section: Resultsmentioning
confidence: 99%
“…Release of the N-glycans from the denatured proteins was performed by adding 1.0 µ L of PNGase F (200 mU), and incubated at 50 °C for 20 minutes. Then, evaporative fluorescent labeling was performed using 4.0 µL of 40 mM APTS in 20% acetic acid, 2.0 µ L of NaBH 3 CN (1 M in THF) and 4 µ L 20% acetic acid as described earlier [24]. The reaction mixture was then incubated in a heating block with open cap at 37 °C overnight under fume hood.…”
Section: Specimen Collection and Sample Preparationmentioning
confidence: 99%
“…The column was filled with HR-NCHO separation gel buffer and the sample was injected after introducing a water plug (1.0 psi for 5.0 s) followed by the sample introduction (2.0 kV for 2.0 s). The N -glycan sample preparation was based on the method introduced by Reider et al ( Reider et al, 2018 ). Briefly, 10 μl of 10 mg/ml (100 µg) bamlanivimab was denatured at 80°C for 10 min using 2.0 µl of a denaturation mixture, followed by digestion with the addition of 1.0 µl of PNGase F in 20 µl of 20 mM ammonium acetate at 37°C for 2.0 h. After the digestion step, 20 µl of the labeling solution was added (6.0 mM of APTS, 100 mM of sodium cyanoborohydride in 1 M THF and 24% of acetic acid) and incubated overnight at 37°C with open lid (evaporative labeling).…”
Section: Methodsmentioning
confidence: 99%